Chapter 2: Rethinking knowledge production through standpoint, decolonisation and intersectionality: thinking with Sandra Harding - Lund, Rebecca W.B (Edward Elgar Publishing, 2023)
This chapter explores the methodology and epistemological interventions of standpoint theory, specifically focusing on the work of feminist philosopher Sandra Harding. The chapter introduces the development of Harding's standpoint theory and shows how it has engaged in dialogue with and contributed to feminism, decolonial theory and intersectionality. In addition, the chapter shows how Institutional Ethnography, as a method-of-inquiry, as an illustration of how standpoint theory can inform research practice. It is argued that standpoint theory is dynamic and open to the adjustments necessary for research in diverging historical, social and cultural contexts, and various social activist agendas. Standpoint theory is only valuable insofar as it is able to affect an expansion of our knowledge and contribute to progressive social development. Standpoint theory offers a promising approach for feminist management and organisation scholars as they engage in the formation of social and critical knowledge that responds to contemporary challenges.